2007
DOI: 10.1016/j.nuclcard.2006.12.325
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of misregistration between SPECT and CT for attenuation-corrected myocardial perfusion SPECT

Abstract: Forty-two percent of the CT attenuation-corrected myocardial perfusion studies had moderate to severe cardiac misregistration qualitatively. Our data suggest that careful review of attenuation correction maps and registration is needed to avoid reconstruction artifacts due to misregistration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 5 publications
3
43
0
2
Order By: Relevance
“…It is relevant that even low-quality CT scans for attenuation correction provide clinically useful information. Goetze et al reported that for 10% of 200 patients, noncardiacrelated abnormal findings were detected (69,70). Similar data with even higher incidence rates are available from cardiac CT studies (74,75).…”
Section: Use Of Ct For Attenuation Correctionmentioning
confidence: 68%
See 1 more Smart Citation
“…It is relevant that even low-quality CT scans for attenuation correction provide clinically useful information. Goetze et al reported that for 10% of 200 patients, noncardiacrelated abnormal findings were detected (69,70). Similar data with even higher incidence rates are available from cardiac CT studies (74,75).…”
Section: Use Of Ct For Attenuation Correctionmentioning
confidence: 68%
“…However, a potential misalignment between emission and transmission data poses the risk of incomplete correction and thus artificial perfusion defects and requires careful quality control to avoid reconstruction artifacts. PET/CT (67,68) and SPECT/CT (69,70) studies have shown that the frequency of misalignment is high (#50%) and that the consequences are clinically significant. Fortunately, a recent study with a digital phantom showed that the effects of misalignment are less severe for SPECT/CT than for PET/CT, mainly because of reduced spatial resolution (71).…”
Section: Use Of Ct For Attenuation Correctionmentioning
confidence: 99%
“…Despite the integration of high-end CT devices with the capability to perform state-of-the-art coronary CT angiography into nuclear scanners to form dedicated cardiac hybrid scanners, manual image coregistration may remain indispensable. Studies with X-ray based attenuation correction have reported that automated coregistration of CT and SPECT images is often unreliable and manual correction for misalignment is needed in the vast majority of the cases (26,27).…”
Section: Definition and General Aspects Of Hybrid Imagingmentioning
confidence: 99%
“…For those SPECT systems equipped with CT attenuation correction devices, an important QA step is to verify correct registration of CT and SPECT transaxial sections, as otherwise perfusion defect artifacts can result. 13 Looking to the future, developments in detector design and reconstruction algorithms have expanded the types of physiologic parameters that can be computed in Nuclear Cardiology, and these newer procedures will require additional QA steps. In recent years, several different SPECT system designs have become available that do not physically rotate around the patient, but rather collect data simultaneously from all projections over a 1808 arc about the patient's thorax.…”
mentioning
confidence: 99%